Molecular Analysis, Pathogenic Mechanisms, and Readthrough Therapy on a Large Cohort of Kabuki Syndrome Patients. Issue 7 (9th April 2014) - Micale, Lucia; Augello, Bartolomeo; Maffeo, Claudia; Selicorni, Angelo; Zucchetti, Federica; Fusco, Carmela; De Nittis, Pasquelena; Pellico, Maria Teresa; Mandriani, Barbara; Fischetto, Rita; Boccone, Loredana; Silengo, Margherita; et al.
<x xml:space="preserve">Abstract</x> In this report, we have expanded the spectrum of mutations of KMT2D and KDM6A genes by analysing our cohort of 303 Kabuki patients by direct sequencing, MLPA and quantitative PCR. Based on KMT2D biological role, we designed functional studies that highlighted the haploinsufficiency of KMT2D as one of the mechanisms underlying the pathogenesis of the disease. Moreover, we provided the first preliminary proof‐of‐concept that occurring nonsense mutations in KMT2D and KDM6A can be effectively suppressed and the functional endogenous protein level and biological activity of KMT2D and KDM6A proteins restored. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>